Development of Teaching Materials and Concept Maps About the Relationship Between Sustainability and Chitosan for Water Treatment: Qualitative Content Analysis - Rachmi Andini, Cita; ., Hernani; Khoerunnisa, Fitri (KnE Social Sciences, 2024)
Chitosan is formed by deacetylation of chitin using strong alkali at high temperatures. The content of the active amine groups in chitosan is widely used as an alternative natural coagulant that is environmentally friendly. So, it can be included in learning materials about the concept of sustainability. This study aimed to produce concept maps and Teaching Learning Sequences (TLS) based on scientists’ conceptions of sustainability on the topic of water treatment using natural coagulants. The method used in this research was qualitative content analysis. The research instruments included content analysis formats and sustainability aspects. The content analysis process included literature collection, descriptive analysis, category selection, and material evaluation with didactic aspects. This research produced concept maps and TLS that described the relationship between water treatment using natural coagulants and colloid content. Additionally, TLS related to sustainability education in the form of learning about water treatment using natural coagulants from chitosan was also developed. The concept map and TLS that have been compiled show the relationship between mapping aspects of scientific literacy and environmentally friendly water treatment using natural coagulants. The research results can be used as a basis for developing teaching materials and didactic designs. Keywords: concept maps, sustainability, chitosan